Beta-Cryptoxanthin Supplementation Protects Against Liver Cancer Progression and Correlates With Altered Targeted and Untargeted Metabolomic Profiles in Mice. (14th June 2022) - Daniels, Michael; Huang, Neil; Dolnikowski, Gregory; Matuszek, Gregory; Lim, Ji Ye; Matthan, Nirupa; Wang, Xiang-Dong
Abstract: Objectives: Nonalcoholic fatty liver disease (NAFLD)-associated hepatocellular carcinoma (HCC) is expected to increase globally in the upcoming years. Diets high in refined carbohydrates and added sugars (HRCD) have been linked to NAFLD progression. Previous studies have demonstrated that retinoids possess anti-tumorigenic properties, yet less is known about whether upstream provitamin A carotenoids exhibit similar characteristics. We recently demonstrated that dietary beta-cryptoxanthin (BCX), a provitamin A carotenoid, decreased NAFLD severity and HCC progression in diethylnitrosamine (DEN)-initiated, high refined carbohydrate diet (HRCD)-fed mice. In this study, we evaluated the effects of dietary BCX supplementation on modulating plasma biomarkers, hepatic vitamin A status, and plasma metabolomic profiles in our DEN-initiated, HRCD-promoted model of HCC. Methods: Male, six-week-old C57BL/6J mice were injected with DEN (25 mg/kg BW) and a fed a HRCD (66.5% carbs including sucrose) with or without BCX supplementation (10 mg/kg diet) for 24 weeks. Using plasma samples, we performed metabolomics using our UHPLC-QTOF-MS platform, a targeted Biocrates MxP Quant 500 kit, and a complimentary untargeted analysis of phospholipids from the METLIN database to identify metabolites which correlate with primary outcomes. Hepatic vitamin A levels were determined via HPLC. Results: Compared to HRCD-fed, DEN-injected mice, mice fed BCX displayed significantly lower tumor burden and steatosis, higher hepatic vitamin A status, and lower plasma levels of alanine transaminase (ALT) and lactate dehydrogenase (LDH). Moderate negative correlations were also identified amongst hepatic vitamin A levels and primary outcomes, such as HCC tumor number, steatosis score, and relevant biomarkers. Our metabolomics data showed significant modulations in metabolites with BCX treatment from phosphatidylcholine, sphingomyelin, ceramide, bile acid, and other phospholipid classes. Conclusions: BCX supplementation significantly reduced HCC severity, increased hepatic vitamin A status, reduced plasma levels of ALT and LDH, and altered several lipid-related classes of metabolites, thus supporting a chemopreventive potential for BCX against HRCD-promoted HCC development. Funding Sources: USDA/ARS and NIFA/AFRI.